PELINDUNGAN DATA PRIBADI DALAM ANALISIS PENYALAHGUNAAN POSISI DOMINAN BERDASARKAN HUKUM PERSAINGAN USAHA - Devina Tanzil; Kristianto P.H. Silalahi (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2022)
AbstractThe development of information and communication technology makes data more developedand has high-value economic commodities which drives the economic activities moredigitalized. From these innovations, society is facilitated in almost every sector of life andbusinesses also benefit from consumers who use their products. To reap these benefits,businesses process personal data. However, when businesses collect and use large amounts ofpersonal data from their users to dominate the market, this has the potential to trigger anticompetitive actions that have an impact on unfair competition among their competitors. Theimportance of data protection is not only important for the data owner itself, but also itspotential for anti-competitive behavior in this digitalization era. Therefore, the relevancebetween personal data processing and business competition in the digital economy needs to bereviewed to find answers to legal issues that may arise.